Binding of Full-Length HIV-1 gp120 to CD4 Induces Structural Reorientation around the gp120 Core - Ashish (Biophysical Society, 2006)
Small-angle x-ray scattering data on the unliganded full-length fully glycosylated HIV-1 gp120, the soluble CD4 (domains 1–2) receptor, and their complex in solution are presented. Ab initio structure restorations using these data provides the first look at the envelope shape for the unliganded and the complexed gp120 molecule. Fitting known crystal structures of the unliganded SIV and the complexed HIV gp120 core regions within our resultant shape constraints reveals movement of the V3 loop upon binding.